Asian medical systems : a comparative study - Leslie, Charles M. (Berkeley : University of California Press, 1976)
This Volume has been designed to show how research on Asian medicine opens a new field of scholarship, the comparative study of medical systems. Such a book requires the skills of authors with many kinds of training and those who have contributed essays to this volume are trained in history, sociology, anthropology, public health, pharmacology, epidemiology, cosmopolitan medicine and philosophy.
Includes bibliographies and index.
Keywords: Medicine, Oriental; Medicine -- Asia; Medical anthropology -- Asia